Karakteristik Pasien Dermatitis Kontak (Iritan dan Alergi) di Puskesmas Tarowang Kabupaten Jeneponto Provinsi Sulawesi Selatan Tahun 2022-2023 - Angraeni, Andi Gita Sentini; Waspodo, Nurelly N.; Arifin, Arina Fathiyyah; Abdi, Dian Amelia; Yuniati, Lisa (Universitas Batanghari Jambi, 2024)
Contact dermatitis is a general term for an acute or chronic inflammatory reaction to a substance that stimulates the skin. This disease can cause work discomfort and reduce worker productivity. Women, babies, the elderly, and those with atopic tendencies are more susceptible to irritant contact dermatitis, while allergic contact dermatitis has risks including age, occupation, and a history of atopic dermatitis. The aim of this study was to determine the characteristics of contact dermatitis patients (irritants and allergies) at the Tarowang Community Health Center, Jeneponto Regency in 2022-2023. This research is a quantitative descriptive study with a research sample of all patients diagnosed with contact dermatitis (irritant and allergic) at the Tarowang Community Health Center and 455 samples were obtained from medical record data. The results of this study show that the incidence of DKA is greater than DKI at the Tarowang Community Health Center in 2022-2023 with the general occupational characteristics of DKI patients being housewives while DKA are fishermen in the 26-45 year age category with the highest number of lesion locations on the hands of this type. The most common gender is female and the therapy used in DKI patients is an antihistamine type cetrizine while in DKA it is an antihistamine type mebihydroline napadisylate.